(untitled) (Bulletin of the Department of Geology, 2013)
The Trisuli Ganga River is rich in sand and gravel which are widely exposed along its banks. In recent years, quarry sites have been established and the materials have been supplied to markets. Apart from it the Trishuli III hydroelectric project is going to be established and for which a huge amount of construction aggregates will be required. From the study of sand and gravel as construction aggregates, it is found that the major composition of the sediments are metamorphosed rocks of the Lesser Himalayan rocks like gneiss, schist, quartzite, metasandstone, slate, granite, phyllite, etc. The gradation of coase aggregates range from dense to gap graded categories. Sulphate soundness value (SSV) and Los Angeles value (LAV) are 1.33–2.28% and 29.9–36.4%, respectively. These ranges show ability of the aggregates to resist weathering and abrasion, and since these values lie within international specifications, the aggregates are suitable for various uses as; both asphaltic and concrete aggregates. Considering the fine aggregates, though they contain considerable amount of quartz grains, also contain exceeding amount of mica, and possesses poor workablity. Fineness modulus ranges between 6.07 and 7.63, and exhibit dominantly sand size. Reduction of mica and further analysis for alkali-silica reactivity will enhance for its potential use. DOI: http://dx.doi.org/10.3126/bdg.v16i0.8883 Bulletin of the Department of Geology Vol. 16, 2013, pp. 43-52